Solve log_2(3x + 7) = 3 + log_2(x – 1), x > 1.

Begin by collecting log_2 terms.log_2(3x + 7) - log_2(x – 1) + = 3 Using the rule of log terms we getlog_2((3x+7)/(x-1)) = 3 (3x+7)/(x-1) = 233x+7 = 8(x-1)3x+7-8x+8 = 0 -5x+15 = 0 x= 3

Answered by Catriona F. Maths tutor

1737 Views

See similar Maths Scottish Highers tutors

Related Maths Scottish Highers answers

All answers ▸

Given that dy/dx = 6x*2 - 3x + 4 And y =14 when x=2. Express y in terms of x


Express '2x^2 + 8x + 30' in the form 'a(x+b)^2 + c'


The line, L, makes an angle of 30 degrees with the positive direction of the x-axis. Find the equation of the line perpendicular to L, passing through (0,-4).


Differentiate 5x^2 - 7x +9


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences